Farmers Attitude Mapping Towards Kisan Mobile Advisory Services - Sarvesh Kumar , SRK Singh; R. C. Sharma (Indian Journal of Extension Education, 2015)
The Kisan Mobile Advisory service (KMA) was initiated by Krishi Vigyan Kendra Harda to deliver messages twice a week to the registered farmers for better utilization of need based information technology in agricultural field and to transfer the innovations and recommended technologies up to grassroot level. The farmers’ attitude towards this programme was reported as favorable. Asample of 200 farmers receiving the KMAservices were selected covering three blocks namely Harda, Khirkiya and Timarani using random sampling method. The majority of the respondent (65.5%) had favorable attitude and 22.5 per cent of the farmers had most favorable attitude towards KMAservices and remaining 12 per cent respondents reported unfavorable attitude towards KMA services. Farmers were satisfied and benefited with the working of KMA services. Information received by farmers under KMA services was found to be need based; understandable and applicable. The farmer’s attitude towards KMA services was positively and significantly associated with age, occupation, education, socio-economic status, knowledge and social-participation, participation in extension activities and size of land holding.